Toxicity of the powdered rhizome of Curcuma longa L. and curcumin - Condorhuamán Figueroa, Martin (2022)
The rhizome of Cucuma longa L. is a plant species used for flavoring and medicinal purposes, therefore, it is important to carry out toxicity studies to determine its safety margins. Objective: to evaluate the acute and chronic toxicity of the powdered rhizome of Curcuma longa L. and curcumin in albino mice and rats. Methodology: it is an experimental investigation. For the acute toxicity test, 36 albino mice of 2 months of age were used, weighing 20 to 25 grams, randomly divided into nine groups of 4 animals, and for chronic toxicity, 30 male albino rats of 10 to 25 grams were used. 12 weeks of age, with an average weight of 200 to 250 grams divided into five groups of 6 animals. The products analyzed were the powdered rhizome of Curcuma longa and curcumin at 95% (p/p) purity. For the acute toxicity test, four groups were formed, at doses of 0.5; 1.0; 1.5; and 2.0 g/kg in solution respectively. For the chronic toxicity test, the Curcuma longa rhizome was used at doses of 200, 400 and 600 mg/kg and curcumin at 20 mg/kg in solution. Hematological evaluation was performed: complete blood count and biochemical: glucose, urea, creatinine, liver profile and lipid profile. Results: The mean lethal dose of Curcuma longa rhizome and curcumin is greater than 2000 mg/kg. In the chronic toxicity test, there was evidence of variation in some hematological and biochemical parameters (p<0.05), but without clinical significance compared to the control group. Conclusion: The powdered rhizome and curcumin did not present toxic effects on experimental animals.